The Role of Tecovirimat in the Management of Monkeypox - Prasetyo, Ari Dwi; Harun Hudari; Mega Permata; Nelda Aprilia Salin (HM Publisher, 2024)
Monkeypox is a self-limited disease with symptoms that disappear within 14 to 21 days. Clinical management of monkeypox includes general supportive care and the use of antivirals that have activity against the monkeypox virus. This literature study aims to describe the role of tecovirimat in the management of monkeypox. Tecovirimat is an antiviral drug approved by the U.S. Food and Drug Administration (FDA) as part of the treatment management of smallpox in adults and children. Evidence of the efficacy of tecovirimat as mpox therapy was obtained from animal studies, where tecovirimat reduced mortality rates, reduced duration of illness and viral shedding. Tecovirimat inhibits the vp37 viral protein encoded by the F13 gene of the variola virus. This protein is highly conserved in orthopoxviruses, allowing tecovirimat to have in vitro activity against several orthopoxviruses, including vaccinia, variola, cowpox, and monkeypox viruses. In conclusion, tecovirimat is used in monkeypox sufferers with severe clinical conditions (sepsis, encephalitis, extensive lesions, bleeding manifestations), patients at risk of experiencing severe clinical conditions (immunocompromised, pregnant or breastfeeding, history of psoriasis, varicella zoster infection) and patients with one or more complications.